PENGARUH PEMBERIAN KOMPENSASI KEGIATAN PENELITIAN DENGAN SISTEM “ORANG JAM (OJ)” TERHADAP PENINGKATAN KINERJA DI PUSAT PEMANFAATAN SAINS ATMOSFER DAN IKLIM – LAPAN - Sudirman Sudirman (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Many factors may influence personnel performance. One among other factors that can motivate employees is proportionate compensation. Having realized its importance, since 2005 there has been a shift in compensation policy from Man-Months to Man-Hours compensation system. This new system provides employees with higher income. The shift in compensation policy is based on the need to improve both personnel performance and personnel wealth at the Centre for Applications of Atmospheric Sciences and Climate. Despite better compensation, based upon writer’s preliminary research, personnel performance has not improved as expected. Better compensation does not seem to have had any impacts on theperformance improvement. However, the research result hints at 0.754 correlation coefficient using Pearson Product Moment correlation analysis. It indicates that there is a strong correlation between Man-Hours Compensation System and personnel performance.